Development of a PTHrP Chemiluminescent Immunoassay to Assess Humoral Hypercalcemia of Malignancy - Ashrafzadeh-Kian, Susan Louise (J Endocr Soc, 2021)
Background: Measurement of parathyroid hormone related peptide (PTHrP) is helpful in the diagnosis and clinical management of patients suspected of humoral hypercalcemia of malignancy (HHM). In these patients uncontrolled release of PTHrP by tumor cells is responsible for the hypercalcemia and PTH concentrations are typically suppressed. Objective: Develop a sensitive and specific assay for quantitation of PTHrP in plasma. Method: Calibrators (PTHrP 1-86) and samples (50uL) were incubated with an anti-PTHrP goat polyclonal acridinium ester labeled antibody. Complexes were transferred and incubated in a microplate coated with an anti-PTHrP polyclonal rabbit antibody. After washing, the acridinium ester generated signal, which is directly proportional to the amount of PTHrP in sample, was quantified. Results: In this assay PTHrp was stable for 24 hours ambient, 3 days refrigerated, 34 days frozen and through 3 freeze/thaws. Intra and inter-assay imprecision in EDTA plasma (~0.16-35.0 pmol/L) ranged from 2.2-8.6% and 5-15%, respectively. The limit of detection was 0.04 pmol/L and the limit of quantitation was 0.16 pmol/L (15% CV). The analytical measuring range was 0.39-50.5 pmol/L (slope of 1.07 and r(2) of 0.99). Average spike recovery was 98% (range 85-108%). The assay was not affected by hemoglobin of ≤500 mg/dL, triglycerides of ≤2000 mg/dL, or bilirubin of ≤50mg/dL. No hook effect was noted up to 500 pmol/L. PTH (1-84) did not cross-react in the assay. C-terminal PTHrP(107-139), and N-terminal PTHrP(1-36) had no significant cross-reactivity (≤1.1%). Mid-PTHrP(38-94) had 8.3% cross-reactivity. Comparison with an in-house PTHrP assay (n=267) showed an r(2) of 0.96, and slope of 2.25 by Passing-Bablok regression fit. The 97.5% reference interval for PTHrP (n=114) was ≤0.7 pmol/L, however a higher concentration (≤4.2 pmol/L) was identified as a more specific clinical cut-off. A retrospective clinical validation study showed that using ≤4.2 pmol/L resulted in a 91% clinical sensitivity and a 98% clinical specificity. Conclusion: We have developed an analytically and clinically sensitive and specific PTHrP immunoassay. A cutoff of ≤4.2 pmol/L is clinically useful in the evaluation of patients suspected of hypercalcemia of malignancy.